Association of meteorological factors and ambient air pollution on medical care utilization for urolithiasis: a population-based time-series study - Tae Il Noh (BMC, 2021)
Abstract Background To identify the association of meteorological factors/ambient air pollutants with medical care utilization for urolithiasis and estimate the effect size/time lags. Methods This is a population-based time-series analysis of 300,000 urolithiasis cases from eight large metropolitan areas in Korea. Seventeen meteorological factors and ambient air pollutants were measured daily during 2002–2017 for each metropolis. Data on daily medical utilization owing to urolithiasis were collected. A generalized additive model was used while factoring in the nonlinear relationship between meteorological factors/ambient air pollutants and urolithiasis and a time lag of ≤10 days. A multivariate analysis was performed. Backward elimination with an Akaike information criterion was used for fitting the multivariate model. Results Urolithiasis was significantly associated with average temperature, diurnal temperature range, sunshine duration, particulate matter (PM) ≤2.5 μm, and carbon monoxide (CO) levels. The incidence of ureteral stones was positively correlated with average temperature, PM ≤2.5 μm level, and CO level (time lags 0–9, 2–4, and 0–9 days, respectively). The incidence of renal stones was positively correlated with PM ≤2.5 μm and CO levels (time lags 2–4 and 0–9 days, respectively). PM ≤2.5 μm (0.05 and 0.07% per 10 μg/m3) and CO (2.05 and 2.25% per 0.1 ppm) conferred the highest excess risk on ureteral and renal stones. Conclusions Urolithiasis is affected by various meteorological factors and ambient air pollutants, PM ≤2.5 μm, and CO levels may be novel potential risk factors for this condition.